Geocell Reinforced Flexible Pavement: Analysis of Strain Induced in Geocell vis-a-vis Thin and Thick-walled Cylinder Theory - Shubham Prakash Shrirao; Parth Rajaram Kulkarni; Sukhanand Sopan Bhosale (International Journal of Sustainable Construction Engineering and Technology, 2023)
Vertical pressure from vehicles on pavement reinforced with geocell develops radial and hoop stresses on geocell walls. Thin-walled cylinder theory is used to estimate the strain induced in geocell by some researchers. It is observed that thin-walled cylinder theory significantly overestimates induced strain when compared with experimental values. This paper presents non-accounted effect of lateral resistance mobilized due to geocell infill soil in computing strain by thin-walled cylinder theory. It is observed that computed strain values using thin-walled cylinder theory accounting lateral resistance match well with experimental results reported in literature. Equivalent thickness (teq) of geocell is then back-calculated by matching the experimental strain values with computed strain values using thin-walled cylinder theory accounting lateral resistance. As the thickness of geocell increases in the form of teq, thick-walled cylinder theory is also studied to analyze the strain induced in the geocell. Combined analysis is then carried out by modifying thick-walled cylinder theory equations using teq derived from thin-walled cylinder theory, and new factor named merging factor (M.F.) is introduced. Results of thick-walled cylinder theory with M.F. match well with experimental strain values reported in literature. Strain computed using modified thin-walled cylinder theory is validated with laboratory results of other researchers.